Analyzing Transition Metal Catalytic Converter Impact on Four-Stroke Motorcycle Fuel Consumption - Ariyanto, Sudirman Rizki; Nugraha, Ata Syifa'; Cahyadi, Wahyu Robby; Dianastiti, Yelma; Pratama, Muhammad Yandi (Universitas Negeri Malang, 2023)
Increased exhaust emissions from motor vehicles have become a major concern in efforts to reduce air pollution. One developed solution is the use of transition metallic catalytic converter (TMCC) technology in vehicle exhaust systems. This study aims to compare the fuel consumption efficiency of three types of exhaust systems, namely standard exhaust without a catalyst (STD WC), the standard exhaust with Original Equipment Manufacturer catalyst (STD OEM), and an exhaust system equipped with a Copper-Coated Chrome Metallic Catalytic Converter (TMCC CuCr). The data analysis method employed a quantitative approach by collecting fuel consumption data at each rpm and analyzing the mean and standard deviation. The research findings indicate that STD OEM has a lower average fuel consumption (0.80 liters per hour) and smaller standard deviation (0.06) compared to TMCC CuCr (0.83 liters per hour and 0.07). Although TMCC CuCr demonstrates good efficiency, STD OEM remains the best choice in terms of fuel efficiency. However, if the differences in fuel consumption and standard deviation are considered insignificant, TMCC CuCr could be a more economical alternative with its affordable price and greater material availability. Furthermore, its fuel consumption performance is not significantly different from that of STD OEM.